The Impact of Accent Bias on Speaking Confidence Among EFL Learners in Indonesia - Budik Kusworo (Universitas Al-Qolam Malang, 2026)
This research explores the impact of accent bias on the speaking confidence of English as a Foreign Language (EFL) students. In various educational contexts, native-like accents, particularly those from American and British speakers, are often idealized, which can create pressure for students to match these accents. Adopting a qualitative approach, the study gathered data through semi-structured text interviews with 20 fourth -semester university students enrolled in an English education program. It is evident that while accent bias may lead Feelings of Insecurity Regarding Accent, social pressure, and Perceptions of the Importance of Accent in Communication, Variation in Speaking Confidence, Impact of Accent Bias on Language Learning, and Relationship Between Confidence and Speaking Ability. The study reveals that a majority of participants feel a societal pressure to adopt native accents, particularly American or British, in order to be perceived as more proficient in speaking. Additionally, some participants reported feelings of inferiority when their accents differed from those of native speakers.